Ler, reformar e escrever: teologia mística na expressão feminina de Teresa de Ávila - Ramos, Joyce de Freitas (2017)
Having the objective of trying to find ways for women to express their selves within the Spanish convents in the XVIth century through the contact with the Mystical Theology, the present work will concentrate on the analyses of sources written by Saint Teresa of Avila. The vast textual production, which guaranteed her the title first Doctor for the Catholic Church, and her reformative movement within the religious life made her a model for female sanctity in her own time and for the following centuries. The study of her work may lead us to realize her place of action and her condition of reader, reformer and writer, all of which are characteristics that seemed unreachable to a woman in Modern Spain